2017
DOI: 10.1158/1078-0432.ccr-16-3155
|View full text |Cite
|
Sign up to set email alerts
|

Early Evaluation of Circulating Tumor DNA as Marker of Therapeutic Efficacy in Metastatic Colorectal Cancer Patients (PLACOL Study)

Abstract: Markers of chemotherapy efficacy in metastatic colorectal cancer (mCRC) are essential for optimization of treatment strategies. We evaluated the applicability of early changes in circulating tumor DNA (ctDNA) as a marker of therapeutic efficacy. This prospective study enrolled consecutive patients with mCRC receiving a first- or second-line chemotherapy. CtDNA was assessed in plasma collected before the first (C), second (C) and/or third (C) chemotherapy cycle, using picodroplet-digital PCR assays based either… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
171
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(190 citation statements)
references
References 32 publications
(39 reference statements)
14
171
1
4
Order By: Relevance
“…Recent studies found a marked prognostic value of ctDNA in OS estimates [24,25]. Our result supports their conclusion, as patients with a plasma mutation were shown to have a significantly worse survival compared to the rest of the cohort (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies found a marked prognostic value of ctDNA in OS estimates [24,25]. Our result supports their conclusion, as patients with a plasma mutation were shown to have a significantly worse survival compared to the rest of the cohort (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Later studies confirmed the predictive value of ctDNA levels for RFS and OS [20,21,48]. In addition, these studies indicated that the amount of ctDNA might be independent of established prognostic factors (age, ECOG performance status, and CEA) [20,21], and that the slope of ctDNA after initiation of treatment adds prognostic information [48]. In a prospective study with 230 stage II CRC patients, subjects with positive ctDNA at first follow-up had a 3-year RFS of 0% in contrast to 90% in the ctDNA-negative patients [83], suggesting that ctDNA might in the future be used to stratify for adjuvant treatment.…”
Section: Prognostic Stratificationmentioning
confidence: 84%
“…In patients with stage I-IV CRC, the detection of KRAS mutations in ctDNA predicted recurrence-free survival (RFS) and OS [82]. Later studies confirmed the predictive value of ctDNA levels for RFS and OS [20,21,48]. In addition, these studies indicated that the amount of ctDNA might be independent of established prognostic factors (age, ECOG performance status, and CEA) [20,21], and that the slope of ctDNA after initiation of treatment adds prognostic information [48].…”
Section: Prognostic Stratificationmentioning
confidence: 96%
See 1 more Smart Citation
“…While informative serum markers are available for the minority of human tumors, the use of blood-based mutation tests for the immediate assessment of treatment efficacy can potentially be applied to every cancer patient, as all malignant neoplasms contain a spectrum of somatic mutations. The utility of circulating tumor DNA for the control of surgical tumor eradication as well as the response to systemic treatment has already been exemplified in a number of studies (Tie et al, 2016; Abbosh et al, 2017; Garlan et al, 2017; Jamal-Hanjani et al, 2017; Goldberg et al, 2018; Lee et al, 2018). A similar approach can be applied for the early detection of tumor relapse.…”
Section: Liquid Biopsymentioning
confidence: 99%